Analysis of the Replication Mechanisms of the Human Papillomavirus Genomes - Liblekas, Lisett; Piirsoo, Alla; Laanemets, Annika; Tombak, Eva-Maria; Laaneväli, Airiin; Ustav, Ene; Ustav, Mart; Piirsoo, Marko (Frontiers in Microbiology, 2021)
The life-cycle of human papillomaviruses includes three distinct phases of the viral genome replication. First, the viral genome is amplified in the infected cells, and this amplification is often accompanied by the oligomerization of the viral genomes. Second stage includes replication of the viral genomes in concert with the host cell genome. The viral genome is further amplified during the third stage of the viral-life cycle, which takes place only in the differentiated keratinocytes. We have previously shown that the HPV18 genomes utilize at least two distinct replication mechanisms during the initial amplification. One of these mechanisms is a well described bidirectional replication via theta type of replication intermediates. The nature of another replication mechanism utilized by HPV18 involves most likely recombination-dependent replication. In this paper we show that the usage of different replication mechanisms is a property shared also by other HPV types, namely HPV11 and HPV5. We further show that the emergence of the recombination dependent replication coincides with the oligomerization of the viral genomes, and is dependent on the replicative DNA polymerases. We also show that the oligomeric genomes of HPV18 replicate almost exclusively using recombination dependent mechanism, whereas monomeric HPV31 genomes replicate bi-directionally during the maintenance phase of the viral life-cycle.